Dietary supplementation of organic selenium to improve growth performance and protein utilization in African catfish fed with different protein level diets - Giri Maruto Darmawangsa; Muhammad Agus Suprayudi; Nurbambang Priyo Utomo; Julie Ekasari (Jurnal Akuakultur Indonesia)
This study aimed to evaluate the effect of organic selenium supplementation on diet with different protein levels on the growth performance and protein utilization of African catfish juvenile. A randomized 2×3 factorial design with two dietary protein levels (27% and 32%) and three dietary selenium (Se) supplementation levels (0 mg/kg, 3 mg/kg, and 6 mg/kg diet) in triplicates were applied in the study. African catfish juvenile with an initial average body weight and body length of 27.00 ± 0.14 g and 15.0 ± 0.5 cm, respectively, was reared in 18 units of aquarium (141 L) at a density of 142 fish/m3 for a rearing period of 40 days. Increasing organic Se supplementation level up to 6 mg/kg at high protein feed resulted in higher fish growth and final biomass, lower FCR, and higher protein utilization efficiency than those of other treatments.  Furthermore, supplementation of organic Se also resulted in lower lipid and higher Se concentrations in the fish body as well as higher blood protein level compared to those of the control. In conclusion, the result of this study suggested that dietary supplementation of organic Se up to 6 mg/kg could enhance the growth and protein utilization in African catfish fed with both low and high protein diet.